Implementing Learner-Centered Teaching in an English Foreign Language (EFL) Classroom - Ardi Marwan (Celt: A Journal of Culture, English Language Teaching & Literature, 2017)
This research was initiated following the widespread claim regarding the success of learner-centered teaching approach across all disciplines. It seeks to examine whether such a claim is true by implementing a theoretical framework of learner centered teaching in an EFL Classroom. A qualitative design involving a teacher of English and a number of learners from a vocational higher institution was used. The findings of this study overall proved that the implementation of this learner-centered teaching framework could make a difference in students’ learning. Their learning became more meaningful, interesting and democratic. Apart from this positive change, it was identified that teacher’s understanding of implementing this framework was still limited resulting in the inconsistency of implementing all aspects of learner centered teaching approach. This study could highlight issues unique to the context of this research but were not covered in the framework. It, therefore, produced an extended framework. Findings from this study can be used for teachers who are interested in implementing the learner-centered teaching approach.